Research on aroma components in different grades of Fuding white tea - CHEN Zhida; WEN Xinli; CHEN Xinghua; CHEN Xianyu; LI Bo; TU Youying (浙江大学学报. 农业与生命科学版)
Headspace solid-phase microextraction and gas chromatography-mass spectrometry were used to study the aroma components and differences of 14 white tea samples of different grades in Fuding of Fujian Province. The results showed that 50 kinds of main aroma components were detected, including leaf alcohol, benzaldehyde, benzyl alcohol, linalool and its oxides. Using heat map, we found that the aroma components of Baihaoyinzhen (BHYZ) and Baimudan (BMD) were similar, and both of them were rich in alcohols with floral aroma. While Shoumei (SM) contained more aldehydes, ketones, esters and lactones, including ionone, dihydroactinidiolide and methyl salicylate. Furthermore, the characteristic aroma components in different grades of white tea were screened by partial least squares-discriminant analysis (PLS-DA). The results showed that the characteristic aroma components of BHYZ were phenylethyl alcohol, cis-jasmone, etc. For BMD, they were β-cedarene, β-elemene, etc; and for SM, they were nerylacetone, ionone and other aroma components. The above results provide a scientific method to determine the main aroma substance in different grades of white tea, and to distinguish the grade of white tea according to the main aroma components.